2018
DOI: 10.5152/turkthoracj.2017.17043
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Serum Metabolic Profile and Lung Function in Chronic Obstructive Pulmonary Disease

Abstract: OBJECTIVES:Although dietary patterns are known to modulate disease severity in patients with chronic obstructive pulmonary disease (COPD), the relationship between the circulating lipid profile and lung function in COPD has not been studied extensively. MATERIAL AND METHODS:There were 43 COPD patients with a history of smoking and 39 patients with a history of biomass fuel exposure recruited in this study, along with 43 age-matched healthy controls. All participants underwent complete lung function profiling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The characteristics of the included studies are summarized in Table 1 . The publication dates of the 11 included studies ranged from 1981 to 2018 [ 13 23 ]. The included studies had been performed in Turkey, Bangladesh, China, Canada, Italy, United States, and India.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are summarized in Table 1 . The publication dates of the 11 included studies ranged from 1981 to 2018 [ 13 23 ]. The included studies had been performed in Turkey, Bangladesh, China, Canada, Italy, United States, and India.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we detected adverse associations with risk of death from RD. A cross-sectional study reported that serum cholesterol level was positively associated with airway resistance in patients with chronic obstructive pulmonary disease [44]. In a murine model of asthma, dietary cholesterol enhanced pulmonary allergic inflammation [45].…”
Section: Plos Medicinementioning
confidence: 99%
“…Based on an a priori evidence of the standard deviation of airway resistance values at 5Hz (R5Hz) of 0.07 kPaL -1 Sec -1 in healthy Indians, 3 with a precision of 5%, an alpha risk of 0.05, and an anticipated non-cooperation rate of 15%, we estimated a total sample size of 202 (101 for each gender). We recruited non-smoking healthy volunteers aged between 18 and 88 years with no clinical history of asthma, COPD, emphysema, allergic rhinitis, respiratory tuberculosis, respiratory infections within four weeks of testing, chest deformity (as observed by chest x-ray); cardiovascular disease; obesity (body mass index >30kg/m 2 ), hospitalization in the last 6 months, pregnancy, or concomitant drug therapy affecting muscarinic and adrenergic receptors.…”
mentioning
confidence: 99%